The bactericidal effect of vancomycin is not altered by tranexamic acid, adrenalin, dexamethasone, or lidocaine in vitro - Christiane Schwerdt (Nature Portfolio, 2021)
Abstract One of the most challenging complications of total knee arthroplasty (TKA) is periprosthetic joint infection (PJI). There is growing evidence of a good anti-infective effect of intrawound vancomycin powder in total joint arthroplasty. At the same time, various different locally applied substances have become popular in total joint arthroplasty. The objective of this study was therefore to investigate a possible inhibition of the bactericidal effect of vancomycin by tranexamic acid, adrenalin, lidocaine, or dexamethasone. The bactericidal effect of vancomycin was quantified using the established method of the agar diffusion test. The plates were incubated with Staphylococcus aureus or Staphylococcus epidermidis and four wells were stamped out. The wells were filled with vancomycin alone, the tested substance alone or a mixture of the two. The fourth well remained empty as a control. The plates were incubated overnight at 37 °C and the zone of inhibition in each field was measured on the next day. All tests were run three times for each pathogen and mean values and standard deviations of the measurements were calculated. Differences between the substances were tested using the t-test at a level of significance of 0.05. The bacterial growth was homogeneous on all plates. The baseline value for the zone of inhibition of vancomycin was on average 6.2 ± 0.4 mm for Staphylococcus aureus and 12 ± 0.3 mm for Staphylococcus epidermidis. In all other substances, no inhibition was detected around the well. The combination of vancomycin and each other substance did not show any different result compared to vancomycin alone. The bactericidal effect of vancomycin on staphylococci is not altered by tranexamic acid, adrenalin, dexamethasone, or lidocaine in vitro.